Effects of the Molecular Weight of Hyaluronic Acid in a Carbon Nanotube Drug Delivery Conjugate - Arpicco, Silvia; Bartkowski, Michał; Barge, Alessandro; Zonari, Daniele; Serpe, Loredana; Milla, Paola; Dosio, Franco; Stella, Barbara; Giordani, Silvia (Frontiers in Chemistry, 2020)
Hyaluronic acid (HA) is a ubiquitous biopolymer involved in many pathophysiological roles. One HA receptor, the cluster of differentiation CD44 protein, is often overexpressed in tumor cells, As such, HA has attracted considerable interest in the development of drug delivery formulations, given its intrinsic targetability towards CD44 overexpressing cells. The present study is focused on examining the correlation of HA molecular weight with its targetability properties. A library of conjugates obtained by linking the amino group of the phospholipid 1,2-dimyristoyl-snglycero-3-phosphoethanolamine (DMPE) to the carboxylic residues of HA of different molecular weight (6.4, 17, 51, 200 & 1500 kDa) were synthesized and fully characterized. The HA-DMPE conjugates were then used to non-covalently functionalize the highly hydrophobic single-walled carbon nanotubes (CNT), and further encapsulate the anticancer drug doxorubicin (DOX). Our results show that the complexes DOX/CNT/HA-DMPE maintain very good and stable dispersibility. Drug release studies indicated a pH-responsive release of the drug from the nanocarrier. Cell viability tests demonstrated that all HA modified CNTs have good biocompatibility, and specific targeting towards cells overexpressing the CD44 receptor. Among all the molecular weights tested, the 200 kDa HA showed the highest increase in cellular uptake and cytotoxic activity. All these promising attributes make CNT/HA200-DMPE a "smart" platform for tumor-targeted delivery of anticancer agents.